Taraxerone inhibits M1 polarization and alleviates sepsis-induced acute lung injury by activating SIRT1 - Lang Deng; Weixi Xie; Miao Lin; Dayan Xiong; Lei Huang; Xiaohua Zhang; Rui Qian; Xiaoting Huang; Siyuan Tang; Wei Liu (BMC, 2024)
Abstract Background Acute lung injury (ALI) is the most lethal disease associated with sepsis, and there is a lack of effective drug treatment. As the major cells of sepsis-induced ALI, macrophages polarize toward the proinflammatory M1 phenotype and secrete multiple inflammatory cytokines to accelerate the disease process through nuclear factor kappa-B (NF-κB) and NLR family pyrin domain containing 3 (NLRP3) inflammasome signaling pathways. Taraxerone, the main component of the Chinese medicinal Sedum, possesses numerous biological activities. However, uncertainty remains regarding the potential of taraxerone to protect against sepsis-induced ALI. This study aimed to investigate the effects and mechanisms of taraxerone against ALI. Methods An animal model for ALI was established by cecal ligation and puncture and treated with taraxerone via intraperitoneal administration. The protective effect of taraxerone on the lungs was analyzed using H&E staining, dihydroethidium staining, ELISA kits, cell counting, myeloperoxidase kit, malondialdehyde kit, glutathione kit, superoxide dismutase kit and flow cytometry. Western blotting, RT-PCR, flow cytometry, co-immunoprecipitation, and immunofluorescence were used to investigate the regulatory of taraxerone on SIRT1. Results Our study demonstrates for the first time that taraxerone can activate SIRT1 in macrophages, promoting SIRT1 activity. This activation inhibited the NF-κB signaling pathway primarily through the dephosphorylation and deacetylation of p65. Simultaneously, taraxerone disrupted the NLRP3 inflammasome signaling pathway, thereby alleviating M1 polarization of macrophages and mitigating sepsis-induced pulmonary inflammation and oxidative stress. In vivo, EX527 was used to validate the anti-inflammatory and anti-oxidative stress effects of taraxerone mediated by SIRT1. Conclusion SIRT1-mediated anti-inflammatory and anti-oxidative stress effects may be important targets for taraxerone in treating ALI.